Wall Street vs main street: Impact of corporations on our lives - Tryfon Korontzis (International Journal of Management, Economics and Social Sciences (IJMESS), 2013)
So many books have been written on corporations but no one seriously thought about the impact on the poor, that is why the seriousness of the issue kept on growing, but the most alarming situation is, business schools and the institutes instead of realizing this issue, they are portraying the corporations as the country saviour (Madeley, 1999). Capitalism bully ascertains finds the Organization for Economic Cooperation and Development (OECD), which primarily deals with the most robust economies in the world. Wilder and widens the inequality between rich and poor. According to OECD in the period 2007-2010, the gap between rich and poor widened longer than the 12 years that have been preceded (Fraczek, 2013). In 33 countries covered by OECD, 10 percent of the wealthiest residents acquire income 9.5 times more than the poorest in 2010, compared with 9 times in 2007. The biggest differences between wealthy and poor citizens appeared in U.S., Turkey, Mexico and Chile. Countries with the smaller comparative deviations are Iceland, Norway, Denmark and Slovenia. Of course, OECD analysts point out that after taxes and social transfers, levels of income inequality and relative poverty in OECD countries was only slightly higher in 2010 as compared to 2007 (OECD, 2011). Data set from 1965 to onward explains that the wealth gap is constantly getting wider and wider between the developed and poor nations (Parente and Prescott, 1993).
Keywords: 330